Posttraumatic Stress Disorders among Adolescent Post the (Islamic State of Iraq and al-Sham) (ISIS) War in Kirkuk City - Iman Hussein Alwan1 , Abid Salih Kumait2 , Hassan A. Hussein3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The gathering of Islamic assembling in Iraq and the Levant was known as the Islamic State in Iraq and the Levant, known as the ISIS, a furnished affiliation that follows the way of thinking of jihadi Salafi social occasions, and whose people point - according to their conviction - to restore “the Islamic caliphate and the utilization of Sharia”, and its people exist and spread Its effect is generally in Iraq and Syria with refreshes on its embodiment in the zones various countries are southern Yemen, Libya, Sinai, Azawad, Somalia, northeastern Nigeria and Pakistan. Additionally, the pioneer of this affiliation is Abu Bakr Al-Baghdadi Objective(s): To assess post-traumatic stress disorders among adolescents after (the Islamic State of Iraq and the Levant War) (ISIS) in the city of Kirkuk. Methodology: A non experimental approach using descriptive design was applied in the present study from 1st october 2019 to the 20th of February 2020. The study was conducted at rual area which was under ISIS at Alhawija district in Kirkuk Gvernorate. the study involve many villige at alhawija district includes (Musaanaa village, Shamlan village Aleaoa village, Alhalawa village, Alkhan village). A Purposive sample consisted of (100) from both (male and female) the sample was collected from five village at alhiwija district,these village was occupied by ISIS groups approximately for 3 years from june,2014 untill october In order to gather the study data, a questionnaire was building depending on the criteria of WHO scale (formate and modify by researcher) and related literature according to their study Data were analyzed by Statistical Package for Social Science (SPSS) version (24) is used for data analysis at. Results: The study revealed the sample size was consist of (57.0%) male and (43.0%) female also the result shows the participants are suffering from moderate to severe level of psychological distress which indicates having low level of psychological wellbeing and general health. Recommendation: National and international interventions are required for them especially for the victims of sexual violence, physical, social and psychological supports are needed. Further studies and researches also required to assess their suffering and other possible psychological disorders.